STRATEGIC APPROACH TO THE MANAGEMENT OF THE FINANCIAL SECURITY OF ENTERPRISES IN THE CONDITIONS OF THE FORMATION OF THE SOCIAL ECONOMY - TULCHINSKIY, Rostislav; KOSTIUNIK, Olena; KRASNOSHAPKA, Volodymyr; POHREBNIAK, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is dedicated to justifying the feasibility of applying a strategic approach to managing the financial security of enterprises in the conditions of the formation of a social economy. Ensuring the financial security of enterprises makes it possible not only to earn profits, but also to increase employment and welfare of the population, as well as to participate more actively in solving social problems of social development. The expediency of using a strategic approach to managing the financial security of enterprises in the conditions of the formation of the social economy is substantiated. It has been established that a strategic approach to the management of the financial security of the enterprise makes it possible to identify the possibilities of ensuring the sustainability of the economic system and the functioning of the enterprise in the long term in the conditions of the formation of the social economy. A strategic approach to the management of the financial security of the enterprise makes it possible to identify the possibilities of ensuring the stability of the economic system and the functioning of the enterprise in the long term in the conditions of the formation of the social economy. It is substantiated that the main areas of strategic management of the financial security of enterprises in the conditions of the formation of a social economy include the following: financial forecasting, risk management, financial control, optimization of the capital structure, financial analysis, liquidity, diversification of investments, strategic planning. It has been proven that the ability and adaptation to the conditions of the surrounding environment is the main guarantee of the financial stability and security of the enterprise. In the conditions of post-war recovery, in order to increase the efficiency of the functioning of the system of financial security of enterprises in the conditions of the formation of the social economy, it is necessary to: form a system of functional competitive strategies of the financial and economic security of enterprises; implement innovative investment strategies aimed at creating new competitive advantages; to introduce the principles of circular economy and ecological production; implement digital technologies, etc.
Keywords: strategic management; financial security; social economy; strategic approach; finance; economic system; efficiency of enterprise functioning; financial analysis